Apache Point Observatory (APO)/SMARTS Flare Star Campaign Observations. I. Blue Wing Asymmetries in Chromospheric Lines during Mid-M-Dwarf Flares from Simultaneous Spectroscopic and Photometric Observation Data - Yuta Notsu; Adam F. Kowalski; Hiroyuki Maehara; Kosuke Namekata; Kenji Hamaguchi; Teruaki Enoto; Isaiah I. Tristan; Suzanne L. Hawley; James R. A. Davenport; Satoshi Honda; Kai Ikuta; Shun Inoue; et al. (The Astrophysical Journal, 2024)
We conducted the time-resolved simultaneous optical spectroscopic and photometric observations of mid-M-dwarf flare stars YZ CMi, EV Lac, and AD Leo. Spectroscopic observations were obtained using Apache Point Observatory 3.5 m and Small and Moderate Aperture Research Telescope System 1.5 m telescopes during 31 nights. Among the 41 detected flares, seven flares showed clear blue wing asymmetries in the H α line, with various correspondences in flare properties. The duration of the blue wing asymmetries range from 20 minutes to 2.5 hr, including a flare showing the shift from blue to red wing asymmetry. Blue wing asymmetries can be observed during both white-light and candidate non-white-light flares. All of the seven flares showed blue wing asymmetries also in the H β line, but there are large varieties on which other chromospheric lines showed blue wing asymmetries. One among the 7 flares was also observed with soft X-ray spectroscopy, which enabled us to estimate the flare magnetic field and length of the flare loop. The line-of-sight velocities of the blueshifted components range from –73 to –122 km s ^−1 . Assuming that the blueshifts were caused by prominence eruptions, the mass of upward-moving plasma was estimated to be 10 ^15 –10 ^19 g, which are roughly on the relation between flare energy and erupting mass expected from solar coronal mass ejections (CMEs). Although further investigations are necessary for understanding the observed various properties, these possible prominence eruptions on M-dwarfs could evolve into CMEs, assuming the similar acceleration mechanism with solar eruptions.